Ductility of thin metal film on a polymer substrate for stretchable electronics. (November 2015) - Chen, R.; Pan, K.; Lin, H.; Wei, N.; Zuo, F.
Abstract : This study investigates the influence of various factors on the ductility of thin metal films on polymer substrates through structural modeling of these polymer-supported metal films using finite element analysis software ABAQUS. The various system parameters include the thickness of the film h, the thickness of the polymer substrate H, the thickness ratio between the film and substrate h/H and the Young's modulus of the substrate Es. The results demonstrate that each parameter influences the ductility of films except the thickness ratio between the film and substrate h/H. Furthermore, an orthogonal experiment is performed to analyze the combined action of the parameters on the ductility of polymer-supported metal films. It can be concluded that the most dominating factor that influences the ductility of films on polymer substrate is the thickness of the thin metal film h, while the Young's modulus of the substrate while Es plays a secondary role.